Evaluation of the protective effect of Cinnamomum Zeylanicum on cadmium testicular toxicity and Nrf2 gene expression in albino rats - Ibrahim, Samer; Y.Abo-Kora, Seham (International Journal of Pharmacology and Toxicology, 2017)
Cadmium is an industrial pollutant that may exert specific toxic effect on mammals. The aim of study was to investigate the protective effect of Cinnamon on male reproductive system of albino rat induced by cadmium toxicity. Forty male albino rats were divided into 4 groups. 1st Â Group administrated saline and kept as control.2nd Group administrated 200mg/kg / day Cinnamon extract. 3rd Group administrated 20mg/kg/day cadmium chloride.4th Group administrated 200mg/kg/day Cinnamon extract and 20mg/kg/day cadmium chloride orally for 8 weeks. . Our results revealed significant decrease in testosterone hormone level, sperm viability, and significant increase in sperm abnormality. An increase in expression of Nrf2 gene was recorded. Pathological changes in testes showed focal degeneration with loss of spermatogenic series in the seminiferous tubules. All of the above mentioned results were significantly improved in 4th group. In conclusion, Cinnamon extract has a protective effect on the testicular damage induced by cadmium chloride.